2021
DOI: 10.3389/fmicb.2021.674160
|View full text |Cite
|
Sign up to set email alerts
|

Deep Soil Layers of Drought-Exposed Forests Harbor Poorly Known Bacterial and Fungal Communities

Abstract: Soil microorganisms such as bacteria and fungi play important roles in the biogeochemical cycling of soil nutrients, because they act as decomposers or are mutualistic or antagonistic symbionts, thereby influencing plant growth and health. In the present study, we investigated the vertical distribution of the soil microbiome to a depth of 2 m in Swiss drought-exposed forests of European beech and oaks on calcareous bedrock. We aimed to disentangle the effects of soil depth, tree (beech, oak), and substrate (so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 108 publications
9
40
0
Order By: Relevance
“…These studies have characterized the diversity of Calonectria species well. Results of a number of other studies indicated that microbial diversity and richness are typically affected by the soil depth [62][63][64][65][66][67], and shallower layers usually have a higher level of microbial diversity [62,63,[66][67][68]. This pattern is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…These studies have characterized the diversity of Calonectria species well. Results of a number of other studies indicated that microbial diversity and richness are typically affected by the soil depth [62][63][64][65][66][67], and shallower layers usually have a higher level of microbial diversity [62,63,[66][67][68]. This pattern is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The sites are covered mainly by European beech (Fagus sylvatica L.) or by oak species (Quercus spp. ), with oak sites having warmer and drier soils than European beech sites (see also Frey et al, 2021). All of the forest stands have a near natural tree species composition originating from natural regeneration and have been unmanaged for several decades (Frey et al, 2021).…”
Section: Forest Sitesmentioning
confidence: 99%
“…), with oak sites having warmer and drier soils than European beech sites (see also Frey et al, 2021). All of the forest stands have a near natural tree species composition originating from natural regeneration and have been unmanaged for several decades (Frey et al, 2021). The forest sites are part of the research platforms WSL Forest Soil Database.…”
Section: Forest Sitesmentioning
confidence: 99%
See 2 more Smart Citations